From Natural Law to Social Welfare: Theoretical Principles and Practical Applications - Epstein, Richard A. (2015)
Many common accounts of natural law understand it in opposition to modern social welfare theory. Contrary to that wisdom, this article shows  how many of the fixed landmarks of the common law, including its rules on individual autonomy and the definition and acquisition of private property, comport with the natural law tradition. t he modern welfarist positions only emerge through key decisions in nineteen century law, which then help explain the choice among three welfarist positions: Kaldor-Hicks, Pareto and a more rigorous standard that requires pro rata gains among all parties. this essay uses a transaction costs framework to explain the proper deployment of these three rules.